Beyond antibiotics: advances in photothermal strategies for oral infections - Wang, Pei; Liang, Jian; Liu, Fen (Frontiers in Bioengineering and Biotechnology, 2025)
The rising prevalence of antibiotic resistance necessitates innovative alternatives for managing polymicrobial oral infections. Photothermal therapy (PTT) emerges as a revolutionary approach that transcends conventional antimicrobial limitations by leveraging near-infrared (NIR)-activated photothermal agents to generate localized hyperthermia, enabling precise biofilm eradication while circumventing systemic drug resistance. The modality capitalizes on the anatomical accessibility of oral tissues and the optical transparency of dental structures, allowing spatiotemporal control over pathogenic niches from superficial caries biofilms to deep periodontal pockets. Recent advances in nanoplatform engineering have unlocked multifunctional PTT systems capable of synergizing thermal ablation with immunomodulation, biofilm matrix penetration, and even tissue regeneration, addressing the dual challenges of microbial persistence and host inflammatory damage. However, clinical translation remains hindered by unresolved technical barriers, including optimal thermal dosage calibration, lesion-specific material design, and long-term biosafety assessment. This review systematically dissects cutting-edge photothermal strategies across the oral infectious spectrum (dental caries, endodontic infections, periodontitis, and peri-implantitis) while critically evaluating their mechanistic innovations in overcoming antibiotic limitations. We further propose a roadmap for next-generation smart PTT systems integrating stimulus-responsive materials and microbiome-aware therapeutic paradigms to achieve personalized oral infection management.